2021
DOI: 10.1016/j.vaccine.2021.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in COVID-19 vaccine acceptance rate among recovered critically Ill patients: A 12-month follow-up study

Abstract: Introduction We surveyed a cohort of patients who recovered from severe SARS-CoV-2 infection to determine the COVID-19 vaccination rate. We also compared the willingness to accept the vaccine before and after its availability to assess changes in perception and attitude towards vaccination. Materials and Methods Recovered patients with severe hypoxemic respiratory failure from SARS-CoV-2 infection treated in the ICU at Grady Memorial Hospital, Atlanta, Georgia between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
3
6
1
Order By: Relevance
“…23 Those with annual influenza vaccine routines may have stronger faith in the benefits of vaccines, predisposing them to remain vaccine willing in the face of misinformation and mass reporting of adverse effects. Among those who have recovered from severe COVID-19 infection, the belief that one was now immune to reinfection was associated with reversal of vaccine willingness, 21 consistent with our findings. Notably, a history of having been tested and engagement in preventive measures against COVID-19 were not identified as significant predictors of vaccine hesitancy in the first round of this survey.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…23 Those with annual influenza vaccine routines may have stronger faith in the benefits of vaccines, predisposing them to remain vaccine willing in the face of misinformation and mass reporting of adverse effects. Among those who have recovered from severe COVID-19 infection, the belief that one was now immune to reinfection was associated with reversal of vaccine willingness, 21 consistent with our findings. Notably, a history of having been tested and engagement in preventive measures against COVID-19 were not identified as significant predictors of vaccine hesitancy in the first round of this survey.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings suggest that the higher the proportion of those in one's vicinity who are vaccinated, the lower the likelihood of becoming vaccine hesitant by the time of follow-up, which is consistent with other studies that have found reversals of vaccine hesitancy to be associated with knowing friends and family members who have been vaccinated and did not experience adverse effects. 21 Prior investigations of the determinants of vaccine hesitancy in Japan have found that a sense of collective responsibility and adherence to subjective norms were associated with a lower likelihood of being unsure or unwilling to receive a vaccine, 7,30 consistent with a culture that places a high premium on conformity. Those who were initially willing to receive vaccination despite believing there to be many disadvantages or few advantages were more easily swayed to hesitancy, suggesting that their initial willingness may have been tenuous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from other studies on key factors are consistent with the findings we obtained. A history of influenza vaccination (which is a recommended vaccination in Poland) is a key factor that affects those willing to vaccinate against COVID-19, while concern about vaccine adverse events or lack of confidence in vaccine efficacy remain the primary factors associated with a lower willingness to vaccinate [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“….4% of those who were undecided, changed their minds and received the vaccine within a year thereafter. 15 Huang et al also found that among people with multiple sclerosis in the United Kingdom, 24.7% and 28.6% of those who responded that they would definitely not and probably not get a COVID-19 vaccine, respectively, received the vaccine within a few months thereafter. 14 On the other hand, a study by Evans et al conducted on healthcare workers in the United States demonstrated that 59.7% of those who previously reported no intention of getting vaccinated against COVID-19 and 90.6% of those who had previously been unsure were vaccinated by follow-up six months later.…”
Section: Discussionmentioning
confidence: 99%